THE TWILIGHT OF US DOLLAR HEGEMONY AND THE COMING MULTIPOLAR WORLD - Krishnan, Armin; Kassab, Hanna Samir (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2024)
The hegemony of the dollar is fundamental to the primacy of the United States in the international system, perhaps even more so than US military superiority. The US government can afford to spend several times more on its armed forces than its military competitors because it has the ability to sustain seemingly unlimited levels of debt thanks to the relative strength of the US dollar. Other nations have been willing to buy US debt and hold large reserves of dollars, which has kept the value of the dollar reasonably stable compared to other currencies. The authors argue that there are clear signs that the dollar's hegemony is in decline and that this could lead to a multipolar world in which the United States is just one great power among others. The article will discuss the reasons why the US dollar is so important to US power, why the dollar's attractiveness is declining and how the unprecedented sanctions imposed by Russia in response to the Russian incursion into Ukraine may have inadvertently accelerated the emergence of a multipolar world.